The Long East Asia
X, 5 p. 8 illus., 6 illus. in color.
Keywords: This book brings together a range of studies that aim at illustrating the ideas, institutions, historical patterns, and contemporary relevance of the social-political system that existed in the main part of East Asia during the premodern era. This is most often known as the Confucian literati-bureaucratic state, the imperial Chinese bureaucratic state, or the Confucian-Legalist state, that was established and endured most notably in China, but also in several East Asian societies such as Korea, Vietnam, Japan. That state and sociopolitical system also greatly shaped state making in several kingdoms in the region – such as Ryukyu and Dali – which were later merged into larger polities. Illuminating the significance of these historical patterns for today, this book will interest political scientists, historians, philosophers, and the general public. Zhengxu Wang is Distinguished Professor at the School of International Relations and Public Affairs Fudan University, China. He obtained his Ph.D. in political Science from University of Michigan, and subsequently obtained academic experiences in the National University of Singapore and the UK’s University of Nottingham, where he served as Associate Professor at its School of Contemporary Chinese Studies and Senior Fellow and Deputy Director of its China Policy Institute. .